Development and Validation of IBSA Photographic Scale for the Assessment of Inner Upper Arm Laxity - Cassuto D; Pellacani G; Tateo A; Artzi O; Ingallina FM; Salti G; Rossi E; Lanzarotti A; Laouedj M; Dapis N; Bellia G (Clinical, Cosmetic and Investigational Dermatology, 2021)
Daniel Cassuto,1 Giovanni Pellacani,2 Antonello Tateo,1 Ofir Artzi,3 Fabio Massimo Ingallina,4 Giovanni Salti,5 Elena Rossi,2 Arturo Lanzarotti,6 Malika Laouedj,7 Nicolas Dapis,7 Gilberto Bellia8 1Private Practice, Milan, Italy; 2Department of Dermatology, University of Modena and Reggio Emilia, Modena, Italy; 3Department of Dermatology, Tel Aviv Sourasky Medical Center, Tel Aviv, Israel; 4Private Practice, Catania, Italy; 5Private Practice, Florence, Italy; 6IBSA Institut Biochimique SA, Lugano, Switzerland; 7Quantificare SA, Valbonne, France; 8IBSA Farmaceutici Italia, Lodi, ItalyCorrespondence: Gilberto BelliaIBSA Farmaceutici Italia, Lodi, ItalyEmail gilberto.bellia@ibsa.itObjective: To describe the development and validation of the 5-grade photographic IBSA inner upper arm scale.Methods: From 2 real-life pictures, a scale made up of 5 morphed images showing increasing severity of inner upper arm laxity was created. For validation, a set of 50 images (half of which real and the other morphed) was developed and sent to 5 trained physicians in two rounds 30 days apart. Raters’ task was to make a selection of each image according to the given scale. Inter-rater and intra-rater reliability were evaluated in both rounds.Results: As to intra-rater reliability, single-rater kappa scores between 0.74 and 1.00 and a global kappa score of 0.846 were observed, while inter-rater agreement was calculated with intra-class correlation coefficient reporting scores higher than 0.91, which indicate excellent reliability.Conclusion: IBSA inner upper arm laxity scale proved to be a validated and reliable tool.Keywords: photographic scale, upper inner arm, laxity, aesthetic medicine, scale validation, scale development